Linear study of the predictive effect of pre-competitive anxiety on coping strategies used by elite footballers U15 registered in the sectorial training centers of the Tunisian Football Federation - Hajji, J.; Elloumi, A. (International Journal of Emergency Mental Health and Human Resilience, 2018)
The abundance of psychological coaching among elite footballers in the sectorial training centers of the Tunisian Football Federation has created a state of ambiguity regarding the two-dimensional treatment of anxiety and coping. The objective of this study is to examine all the predictive relations existing between the different dimensions of precompetitive anxiety and the different coping strategies used by our elites, and the indirect relations through the mediation of coaching, of experience and the technical position, and to understand if the management of anxiety suits their level of elite. These interaction relationships were statistically processed through multiple linear regression analyses to examine direct predictive interaction and through PROCESS v2.16.3 macro model 4, (Hayes Andrew et al., 2013), to examine indirect predictive interactions. The results indicate that the different dimensions of pre-competitive anxiety directly explained all coping strategies used by our elites. On the other hand, all existing indirect predictive relationships have been explained by the effect of mediation and the technical position of the coach.